2016
DOI: 10.1186/s12885-016-2620-7
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the miR-141/200c cluster promotes the migratory and invasive ability of triple-negative breast cancer cells through the activation of the FAK and PI3K/AKT signaling pathways by secreting VEGF-A

Abstract: BackgroundThe role of microRNA-200 (miR-200) family members in the migration and invasion of breast cancer is controversial. This study investigated the mechanisms by which the miR-200 family members modulated the migratory and invasive abilities of an aggressive triple-negative breast cancer (TNBC) cell line, MDA-MB-231.MethodsThe miR-200 family (miR-200b/200a/429 and miR-141/200c clusters) and green fluorescence protein (GFP) were transduced into MDA-MB-231 cells using a lentiviral system. Stable cells highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 36 publications
1
43
0
Order By: Relevance
“…The hsa-miR-141-5p is the less abundant product from the same pre-miRNA with hsa-miR-141-3p and may in fact represent a surrogate measurement of hsa-miR-141-3p. Overexpression of hsa-miR-141-3p and its family member hsa-miR-200c-3p in MDA-MB-231 breast cancer cells promotes significant migration and invasion and enhances VEGF-A secretion [50]. VEGF-A neutralizing antibodies abrogate these phenotypic consequences conferred by hsa-miR-141-3p and hsa-miR-200c-3p overexpression [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hsa-miR-141-5p is the less abundant product from the same pre-miRNA with hsa-miR-141-3p and may in fact represent a surrogate measurement of hsa-miR-141-3p. Overexpression of hsa-miR-141-3p and its family member hsa-miR-200c-3p in MDA-MB-231 breast cancer cells promotes significant migration and invasion and enhances VEGF-A secretion [50]. VEGF-A neutralizing antibodies abrogate these phenotypic consequences conferred by hsa-miR-141-3p and hsa-miR-200c-3p overexpression [50].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of hsa-miR-141-3p and its family member hsa-miR-200c-3p in MDA-MB-231 breast cancer cells promotes significant migration and invasion and enhances VEGF-A secretion [50]. VEGF-A neutralizing antibodies abrogate these phenotypic consequences conferred by hsa-miR-141-3p and hsa-miR-200c-3p overexpression [50]. hsa-miR-449a targets cysteine-rich intestinal protein 2 (CRIP2) mRNA, a transcription factor and a tumor suppressor [51].…”
Section: Discussionmentioning
confidence: 99%
“…Jia et al (31) reported that miR-490-3p could suppress the growth and invasion of TNBC by inhibiting tankyrase-2 expression. Choi et al (32) indicated that miR-141/200c was involved in TNBC migration and invasion via activating the focal adhesion kinase and phosphoinositide 3-kinase/AKT signaling pathways. miRNA-454 was revealed to be associated with poor prognosis in TNBC (17) and miRNA-200b could suppress TNBC metastasis by regulating protein kinase C α (19).…”
Section: Discussionmentioning
confidence: 99%
“…Our preliminary studies showed that miR-200c/141 cluster overexpression in a triple-negative (TN) human BCC line, MDA-MB-231, which lacks estrogen receptor (ER), progesterone receptor (PR) and human epidermal receptor 2 (HER2) expression, enhances the migration and invasion abilities [12], upregulates SerpinB2 and promotes lymph node (LN) and lung metastasis in mouse models. SerpinB2, also known as plasminogen activator inhibitor-2 (PAI-2), inhibits urokinase plasminogen activator (uPA) activity [1315].…”
Section: Introductionmentioning
confidence: 99%